Advances in imaging angiogenesis and inflammation in atherosclerosis - Zagorchev, Lyubomir; Mulligan-Kehoe, Mary Jo (Thrombosis and Haemostasis, 2011)
Advances in imaging technology have provided powerful tools for dissecting the angiogenic and inflammatory aspects of atherosclerosis. Improved technology along with multi-modal approaches has expanded the utilisation of imaging. Recent advances provide the ability to better define structure and development of angiogenic vessels, identify relationships between inflammatory mediators and the vessel wall, validate biological effects of anti-inflammatory and anti-angiogenic drugs, delivery and/or targeting specific molecules to inflammatory regions of atherosclerotic plaques.
Keywords: Atherosclerosis; inflammation; angiogenesis; imaging